Efficient Aerobic Oxidation of Glucose to Gluconic Acid over Activated Carbon‐Supported Gold Clusters. Issue 9 (11th April 2017) - Liu, Chao; Zhang, Junying; Huang, Jiahui; Zhang, Chaolei; Hong, Feng; Zhou, Yang; Li, Gao; Haruta, Masatake
Abstract: The catalytic performance of the atomically precise gold cluster‐Au38 (PET)24 (PET=2‐phenylethanethiolate), immobilized on activated carbon (AC), was investigated for the aerobic oxidation of glucose to gluconic acid. The Au38 (PET)24 /AC‐120 catalysts, annealed at 120 °C in air, exhibited high catalytic activity and significantly better performance than the corresponding catalysts Au38 /AC‐150 and Au38 /AC‐300 (treated at 150 and 300 °C to remove the protecting thiolate ligands). The high activity of the robust Au cluster was a result of the partial ligand removal, providing catalytically active sites, which were evidenced by TEM, X‐ray photoelectron spectroscopy, thermogravimetric analysis, and Fourier‐transform IR spectroscopy. Au38 (PET)24 /AC‐120 also showed excellent recyclability (up to seven cycles). The turnover frequency for the Au38 (PET)24 /AC‐120 catalyst was 5440 h −1, which is higher than for the Pd/AC, Pd‐Bi/AC, and Au/AC under identical reaction conditions. This new ultra‐small gold nanomaterial is expected to find wide application in other catalytic oxidations. Abstract : Solid gold : The catalytic performance of the atomically precise gold cluster‐Au38 (PET)24 (PET=2‐phenylethanethiolate), immobilized on activated carbon, is investigated for the aerobic oxidation of glucose to gluconic acid. The turnover frequency for the Au38 /AC‐120 (AC=activated carbon) catalyst is 5440 h −1, which is higher than for Pd/AC, Pd‐Bi/AC, and Au/AC.